Influence of protaper finishing files and sodium hypochlorite on cleaning and shaping of mandibuldar central incisors - a histological analysis (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study investigated the influence of the last apical instrument of the ProTaper system with and without 2.5% sodium hypochlorite for cleaning mandibular central incisors. MATERIAL AND METHODS: Thirty two mandibular central incisors were divided into six study groups: Group I - F1 instrument with 2.5% sodium hypochlorite; Group II - F1 and F2 with 2.5% sodium hypochlorite; Group III - F1, F2 and F3 with 2.5% sodium hypochlorite; Group IV - F1 with distilled water; Group V - F1 and F2 with distilled water; Group VI - F1, F2 and F3 with distilled water. The two remaining teeth comprised the negative control group. The specimens were prepared following the principles of the technique suggested by the manufacturer and then submitted to histological preparation and morphometric analysis. Data were analyzed statistically by the Kruskal Wallis test at 1% significance level. RESULTS: There was statistically significant difference (p